NEOLIBERALISME DAN DAMPAKNYA BAGI PENDIDIKAN INDONESIA: SEBUAH REFLEKSI - Salim, Agus; Manubey, Johana; Kuswandi, Dedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2023)
In Indonesian education, this neoliberalism ideology is reflected in the increasing role of private educational institutions, the commercialization of education, and the rising cost of education. The result is negative impacts such as access inequality, declining education quality, and the influence of globalization that threatens local cultural identity. This research uses a literature review to explore neoliberalism's impact on Indonesia's education system. Data collection is done through scientific journals, then analyzed and discussed deductively-inductively. As an economic ideology championing market freedom, privatization, and deregulation, neoliberalism impacts education globally, including in Indonesia. The results of the literature analysis found that neoliberalism encourages the marketization of education, privatization of education, deregulation, and competition. Neoliberalism promotes social inequality, where the rich can access the best education while the poor can’t. To deal with neoliberalism and provide access to proper education for the community, the government first needs to increase supervision in education. Second, review the curriculum to include local values, promote cultural pluralism, and prepare students for global challenges. Third, provide holistic-inclusive education. Fourth, actively involving the community in education planning and decision-making. With these steps, Indonesian education can find the right balance between following the principles of neoliberalism that allow for innovation and efficiency while maintaining intrinsic values and providing equal access to education.